Common Turkic vocabulary in the names of tools of the Yakut language (lexical parallels in the Turkic languages of Siberia) - Skryabina, Alevtina A. (The New Research of Tuva, 2024)
The article examines the names of tools in the Yakut language, which are of common Turkic origin, in comparison with related Altai, Khakass, and Tuvan languages. Dictionary of the Yakut language edited by E. K. Pekarsky, A large explanatory dictionary of the Yakut language in 15 volumes edited by P. A. Sleptsov, Altai-Russian Dictionary edited by A. E. Chumakaev and others, Khakass-Russian Dictionary edited by O. V. Subrakova; and the Tuvan-Russian Dictionary edited by E. R. Tenishev, were the sources for the research.Based on the spheres of use, the author has divided the names of tools in the Yakut language into 7 categories: 1) tools for cattle breeding, 2) hunting, 3) fishing, 4) agriculture, 5) household use, 6) wood processing, and 7) leather and fur processing. It was found that many archaic words exist in the studied vocabulary, which can be associated with various changes in life and the restructuring of daily life and traditions among the Yakuts.The study of lexical and semantic parallels between the Yakut, Altai, Khakass, and Tuvan languages through the names of tools has revealed 12 common Turkic origins, confirming the ancient kinship between these languages and their historical interactions.
Keywords: Yakut language; Altai language; Khakass language; Tuvan language; household vocabulary; tools